Clinical Picture, Outcome, and Risk of Serious Bacterial Infections in Immunocompetent Previously Healthy Neutropenic Children - Arslantas, Esra; Aycicek, Ali; Türkoglu, Recep; Tahtakesen, Tuba Nur; Uysalol, Ezgi Paslı; Bayram, Cengiz; Akici, Ferhan; Sanlı, Kamuran; Özdemir, Nihal (Journal of Pediatric Infectious Diseases, 2021)
Objective In childhood, the cause of neutropenia is a challenging diagnosis with a spectrum of underlying etiologies. This study was performed to investigate the clinical picture and the outcomes associated with the new onset neutropenia in previously healthy children, and to determine the risk of serious bacterial infection (SBI) in those patients.Methods Patients presenting between January 2018 and September 2018 with an absolute neutrophil count (ANC) <1,500/μL were retrospectively evaluated. Patients with known underlying chronic disease or immunosuppressive conditions were excluded. Neutropenia was categorized into three groups: mild, 1,000–1,500/μL; moderate, 500 to <1,000/μL; and severe <500/μL.Results A total of 423 patients were investigated. There were 156 (36.9%), 193 (45.6%), and 74 (17.5%) patients in the mild, moderate, and severe groups, respectively. Bacteremia was detected in one (0.02%) patient and SBI in 21 (4.9%) patients. No significant correlation was found between the incidence of SBI and bacterial infection rate among different age groups (p > 0.05). The incidence of SBI varied significantly according to the severity of the neutropenia (p = 0.012) and as the neutropenia became more severe, the incidence of SBI increased (p = 0.015).Conclusion The clinical outcome of neutropenia in previously healthy and immunocompetent children is generally good with a relatively low incidence of SBI. We suggest that aggressive therapy and frequent follow-up should be reserved for previously healthy neutropenic children with SBI.
Keywords: serious bacterial infection; neutropenia; immunocompetent; child